"Too much of a good thing?": exploring the dark side of empowering leadership by linking it with unethical pro-organizational behavior. Issue 1 (13th October 2020) - Zhang, Xue; Tian, Guyang; Ma, Chao; Tian, Yezhuang; Li, Zhongqiu; Liang, Liang
Abstract : Purpose: Grounded in social exchange theory (SET), the purpose of this paper is to examine the relationship between empowering leadership and unethical pro-organizational behavior (UPB), as mediated by duty orientation (including duty to members, duty to mission and duty to codes). Further, this study proposes that perceived leader expediency moderates indirectly between empowering leadership and UPB. Design/methodology/approach: This paper tests this social exchange model across a survey study using time-lagged data collections from 215 employees of a service company in China. Findings: The results show that duty orientation mediates the relationship between empowering leadership and UPB. In addition, perceived leader expediency moderates the indirect relationship between empowering leadership and UPB through duty orientation (i.e. duty to members and duty to missions). Originality/value: This research aids in understanding the impact of empowering leadership on follower outcomes by investigating the dark side of empowering leadership and examining the relationships between empowering leadership, duty orientation and UPB. The present study also challenges the notion that the phrase "the greater the empowerment, the better the outcomes" suggests that organizations should offer a conditional approach to the empowerment of followers by their leaders.